If times change, should we throw away the hearthstone? Exploring (Dis) continuities in autonomy and decision-making in the lives of Ghanaian women - Dzokoto, Vivian A. A.; Darkwah, Akosua K. (Frontiers in Psychology, 2014)
This paper attempts to investigate continuities and discontinuities between traditional and modern representations of womanhood and female gender roles focusing primarily on family and work settings. Using approaches informed by Sociology, Cultural Psychology, and African Studies, the paper explores traditional views of womanhood encapsulated in (and also transmitted intergenerationally) through proverbs. This customary perspective is contrasted with the results of the Everyday Lives Survey from the Pathways of Women's Empowerment Ghana project. The survey investigated the nature of everyday life– education, work, decision making, access to institutions, and autonomy in relationships - in six hundred (600) adult women in both rural and urban communities in three regions of Ghana. We argue that although the times are changing, Ghanaian women who live in a culture that values an interdependent way of being have not changed statistically significantly so far as issues of autonomy and decision-making are concerned.